Reading Too Near, Seeing Television, Using Gagets or Computers in a Long Time and the Decrease of Visual Acuity in School Aged Children in the Elementary School - Heru Sulistijono; Bambang Heriyanto (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2019)
Attention to vision disorders, technological progress is one of the things that might cause visual disturbances. The facts that occur a lot in the field, there are so many children who are familiar with gadgets or PC. The general purpose of this study is to obtain a description of the get us to factors of reading, seeing TV, gaget, PC that affect the decrease of visual acuity in school-aged children. The subject were 30 students in the grade 4-6 of elementary school Kemayoran 1 Surabaya, selected by purposive sampling. Data was collected through by questionnaire. The conclusion is that the get us to factor affects the decreased sharpness of the respondent’s vision. Keywords: get us to factor; decreased sharpness of vision; school-aged children